Association between Perceived Sleep Disorders and SleepRelated Factors among Patients on Methadone Maintenance Therapy (MMT) in Malaysia - Nasir, Mohamad; Mainul, Haque; Zalina, Zahari (2016)
Objectives: Sleep disorders were frequently reported by opioid-dependent patients during methadone maintenance therapy (MMT). This research has determined if there is an association between sleep and sleep-related factors among patients on MMT.